Diet and Brain Health - Pooja N. Tolani; Wendy J. Dahl (EDIS)
Following a healthful diet provides many benefits throughout the life cycle. Maintaining good eating habits as we age can be especially helpful to preserve cognitive health (the ability to remember, learn, and make decisions). This 3-page publication provides tips for healthful eating that may help to maximize brain health in older adults. Written by Pooja Tolani and Wendy J. Dahl and published by the UF/IFAS Department of Food Science and Human Nutrition, January 2018. http://edis.ifas.ufl.edu/fs304